The Effectiveness of Product Placement in Tamil movies: A Study with Reference to the State of Tamil Nadu, India - Kumar, S. Dinesh; Soundarapandiyan, K. (South Asian Journal of Social Sciences and Humanities, 2022)
This study endeavors to enquire the power of item arrangements in Tamil motion pictures. The past surveys are more focused towards Hollywood films, and the majority of the Indian examinations are concentrated towards Hindi motion pictures. Subsequently, there exists a critical hole for this flow exploration to discover the viability of item position and item advancement in the films. The review bargains on Tamil films, VIP support, buyer mentality, corporate believability, brand picture and buy expectation are thought about to foster the speculations. The review was led utilizing an organized poll which was coursed among 3500 film circumvents Tamil Nadu. The investigation was achieved utilizing Visual PLS and SPSS. The consequences of this examination demonstrate that item situations really do have compelling exploration among Tamil crowds, which likewise has a positive relationship with buy goal.